Prognosis of leaching zones distribution in carbonate reservoirs - A. A. Tchistiakov; K. O. Zudina; A. R. Davletshina; E. V. Shvalyuk; V. E. Baranov (Georesursy, 2024)
The proposed method of predicting spatial distribution of leaching zones in carbonate reservoirs includes integrated interpretation of well logging data, including electrical microimages (Formation MicroImager – FMI), together with analysis of lithofacies within depositional cycles. Based on the comparison of FMI data with results of lithological and petrophysical studies of the core, an atlas of diagenetic porosity images for the studied formation was developed. Choquette and Pray international classification was used for pore typing. Applying the developed atlas to FMI logs, karstification zones were identified and classified in reference wells. In wells, where only standard well loggings was performed, karstification zones were identified using a developed decision tree. Sedimentological and sequence stratigraphic analysis made it possible to identify sedimentation cycles and to correlate the main lithofacies within the target reservoir. It was established that microbial and shallow facies form the most productive part of the reservoir. These facies with initially high primary porosity were subjected to the most intensive karstification along sequence stratigraphic boundaries due to subaerial exposure. The established relationships between leaching zones, lithofacies, and sequence-stratigraphic boundaries made it possible to carry out inter-well correlation of karstified intervals. The correlation will allow construction of leaching zones maps, that will be further applied for geological modeling.